Read all about it! - Bush, Laura Welch, 1946-; Bush, Jenna; Brunkus, Denise (New York, N.Y. : HarperCollinsPublishers, 2008)
Tyrone and his friends rule the school except for the library, which he thinks is boring until strange happenings during story hour change his mind.
004-008.
Keywords: Books and reading -- Juvenile fiction; Schools -- Juvenile fiction